2010
DOI: 10.3311/pp.ci.2010-1.06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating on the physical properties of asphalt aggregates

Abstract: Asphalt is defined as a mixture of inert mineral matter, such as aggregate, mineral filler and bituminous binder in predeterminated portions. One of the most important properties of asphalt mixtures is the bitumen content. The most preferred way of asphalt binder analysis is extraction (with tricloroethylene). Because of environmental reasons extraction should be replaced with more environment friendly solution, this could be heating. But high temperatures can cause changes in the physical properties of minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In contrast, asphalt concrete behaves elastically at high loading speeds or low temperatures (Yusupov et al, 2020). Devecseri (2010) also showed that asphalt concrete behaves differently after burning at high temperatures. Thus, using the behaviour of viscoelastic materials for the AC layer in a railway structure provides accurate results in terms of dynamic responses.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, asphalt concrete behaves elastically at high loading speeds or low temperatures (Yusupov et al, 2020). Devecseri (2010) also showed that asphalt concrete behaves differently after burning at high temperatures. Thus, using the behaviour of viscoelastic materials for the AC layer in a railway structure provides accurate results in terms of dynamic responses.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have identified many interrelated factors such as; source of bitumen, bitumen type, absorption, production temperature and silo storage time etc. [11,12] The results of their studies have depicted that, laboratory aging procedures brought in similar properties to the bitumen with the field aging [6,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Many ways of asphalt bitumen measurements exist such as solvent extraction using trichloroethylene, solvent extraction using an alternative solvent, ignition oven, ignition oven and solvent combination [38]. In order to determine the bitumen content within the aged bituminous mixtures, ten batches (each of 1000 grams) of RAP were prepared and extraction test was performed on each of the batch with a laboratory type centrifuge extractor called Rota Test.…”
Section: Determining Properties Of Rapmentioning
confidence: 99%